2019
DOI: 10.1002/anie.201813037
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Carbon: A General Feature of Noble Metals

Abstract: Carbon moieties on late transition metals are regarded as poisoning agents in heterogeneous catalysis. Recent studies show the promoting catalytic role of subsurface C atoms in Pd surfaces and their existence in Ni and Pt surfaces. Here energetic and kinetic evidence obtained by accurate simulations on surface and nanoparticle models shows that such subsurface C species are a general issue to consider even in coinage noble‐metal systems. Subsurface C is the most stable situation in densely packed (111) surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…The diffusion of a C adatom from a H site (State 1 in Figure 3c) to a neighboring degenerate F site (State 2 in Figure 3c) goes through a B site as the saddle point (TS1 in Figure 3c) and experiences an activation barrier of 0.64 eV (Figure 3a), close to the reported activation barrier (0.72 eV). 35 Then, the C atom directly sinks from the F site to the underlying O h site in Sub 1 (State 3 in Figure 3c), whose activation barrier is 0.38 eV, which agrees well with the result obtained from a similar 3 × 3 slab model (0.42 eV) 36 and is evidently lower than the result obtained from a smaller 2 × 2 supercell model (0.67 eV). 35 In the transition state (TS2 in Figure 3c), the C atom squeezes into the Pd surface layer, and the three Pd−C bonds are about 184 pm.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The diffusion of a C adatom from a H site (State 1 in Figure 3c) to a neighboring degenerate F site (State 2 in Figure 3c) goes through a B site as the saddle point (TS1 in Figure 3c) and experiences an activation barrier of 0.64 eV (Figure 3a), close to the reported activation barrier (0.72 eV). 35 Then, the C atom directly sinks from the F site to the underlying O h site in Sub 1 (State 3 in Figure 3c), whose activation barrier is 0.38 eV, which agrees well with the result obtained from a similar 3 × 3 slab model (0.42 eV) 36 and is evidently lower than the result obtained from a smaller 2 × 2 supercell model (0.67 eV). 35 In the transition state (TS2 in Figure 3c), the C atom squeezes into the Pd surface layer, and the three Pd−C bonds are about 184 pm.…”
Section: Resultssupporting
confidence: 84%
“…Actually, the same degeneracy of the H and F sites for C adsorption has also been found for other fcc metals, such as Cu, Ag, and Au. 36 Next, the C−C lateral interaction is studied for the C adatoms. In a two-C model, one H site on the Pd(111) surface is occupied by a C atom, and a second C atom is placed at a nearby site of the occupied H site.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, according to the theoretical work of Piqué et al, the accommodation of carbon atoms in the subsurface region would be favorable for most late transition metals [143]. The influence of carbide phase formation at the surface of cobalt on Fisher-Tropsch catalysis is a long-standing debate [56,144].…”
Section: Compound Formation Including Oxide Sulfide and Carbidementioning
confidence: 99%
“…DFT was also used by Illas et al to investigate C incorporation in subsurface sites of Cu, Ag and Au by using a supercell slab model and a well-shaped nanoparticle model. 57 They reported that the most stable carbon site for the (111) surfaces of Cu and Ag is at the interstitial site, which is also true for their nanoparticle. In contrast, for the Au(111) slab surface, carbon is most stable chemisorbed on the surface, rather than integrated into the structure.…”
Section: Computational Investigationmentioning
confidence: 87%